Pengaruh Laba Bersih dan Debt to Equity Ratio terhadap Dividen pada PT. Adaro Energy Tbk 2010 - 2017 - Utami, Septi; Norisanti, Nor; Mulya Z, Faizal (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2019)
The purpose of this study was to study the effect of net income and the Debt Ratio on Equity to Dividends at PT. Adaro Energy Tbk 2010-2017. The technique used in this study was purposive sampling. The population used in this study is the financial statements of PT. Adaro Energy Tbk, which is listed on the IDX. And the sample from financial statements is available for 32 periods (quarterly). The results of the determination coefficient test (R2) of 0.253 can be interpreted that the effect of Net Profit and Debt To Equity Ratio to Dividend is 25.3%. The remaining 74.4% is influenced by other factors not explained in this study. Based on the multiple correlation coefficient test seen from the R value of 0.503, indicating that there is a moderate relationship between Net Profit and Debt To Equity Ratio with Dividends. Based on the F test the probability value sig. 0.015 <0.05 which means that together the value of Net Profit (X1) and Debt To Equity Ratio (X2) have a significant effect on dividends (Y). Based on the t test shows that Net Profit (X1) does not significantly influence dividend (Y), Debt To Equity Ratio (X2) does not significantly influence dividend (Y).